A prospective study on COVID‐19 convalescent plasma donor (CCP) recruitment strategies in a resource constrained blood centre. (1st June 2021) - Biswas, Durba; Maiti, Chikam; Talukder, Biplabendu; Azharuddin, Md; Saha, Sayantan; Pandey, Sumita; Das, Arijit; Adhikari, Setu Das; Ray, Yogiraj; Sarkar, Biswanath S.; Paul, Sekhar R.; Saha, Bibhuti; et al.
Abstract : Background and Objectives: The COVID‐19 pandemic has spread across 87 million people with more than 1·8 million deaths in the world. As there is no definite treatment modality, the use of convalescent plasma has become increasingly popular worldwide. This study aimed to identify an appropriate strategy of donor recruitment and to evaluate the appropriateness of pre‐set plasma donation guidelines. Material and Methods: In this prospective study conducted from May to September 2020, the donors were recruited under the following two circumstances: Group I, patients in the post–COVID‐19 follow‐up in the clinic, and Group II, patients recovered from COVID‐19 recruited through mass and electronic media. A pre‐set donor selection criteria and laboratory investigation was designed according to national and international guidelines. Approximately 500 ml of COVID‐19 convalescent plasma (CCP) was collected from recovered individuals in each group by two different cell separators. The overall donor's attendance rate, deferral rate, adverse events and donor compliance was analysed and compared between the two groups. Results: There was a significant difference in attendance in relation to registration between the groups ( P  < 0·0001). Donor deferral was significantly higher in group II compared with group I. The single most frequent cause of donor deferral was low antibody index ( P  = 0·0001). The total donor adverse event rate in CCP donation was significantly lower compared with routine plateletpheresis procedures. The donor's compliance to blood centre's protocol was satisfactory in both the groups. Conclusion: Recruitment of patients in the post–COVID‐19 follow‐up in the clinic was more effective than the general recruitment through mass and electronic media for convalescence plasma donation in a resource‐constrained blood centre.